Body Image Dissatisfaction and Eating‐Related Psychopathology in Trans Individuals: A Matched Control Study. (5th May 2015) - Witcomb, Gemma L.; Bouman, Walter Pierre; Brewin, Nicola; Richards, Christina; Fernandez‐Aranda, Fernando; Arcelus, Jon
Abstract High levels of body dissatisfaction have already been reported in the trans population; however, the root of this dissatisfaction, and its association with eating disordered behaviours, has not been studied in‐depth. This study aims to assess eating disorder risk by comparing 200 trans people, 200 people with eating disorders and 200 control participants' scores on three subscales of the Eating Disorders Inventory‐2 (EDI‐2) and to further explore dissatisfaction in the trans participants using the Hamburg Body Drawing Scale (HBDS). The results showed that overall participants with eating disorders scored higher than trans or control groups on all EDI‐2 measures, but that trans individuals had greater body dissatisfaction than control participants and, importantly, trans males had comparable body dissatisfaction scores to eating disordered males. Drive for thinness was greater in females (cis and trans) compared with males. In relation to HBDS body dissatisfaction, both trans males and trans females reported greatest dissatisfaction not only for gender‐identifying body parts but also for body shape and weight. Overall, trans males may be at particular risk for eating disordered psychopathology and other body image‐related behaviours. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.